Analisis Faktor-Faktor yang Berpengaruh terhadap Kemitraan Sapi Perah dengan Metode Structure Equation Modelling - Nuraini, Candra; Imelda, Berli Prissy; Sumarsih, Enok; Mutolib, Abdul (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This research aims to determine the determinants that affect the partnership between dairy farmers and KSU Karya Nugraha. This research was carried out in Cigugur District, Kuningan Regency, West Java, which was determined purposively, the largest milk-producing cooperative in Kuningan Regency. Data collection was carried out from January to September 2020. The study used the dependent variable of partnership, and independent variables are communication, cooperation, trust, and commitment. The survey was conducted to collect information using questionnaires with the number of respondents 42 people selected at random. Data is processed by the SEM-PLS method. The results showed only one insignificant determinant of the partnership was cooperation. Communication, trust, and commitment have a significant effect on alliances. Research has also found that communication and responsibility have a significant influence on collaboration and trust